4 Snow'd in: translating research into practice. (1st September 2016) - Hanson, Dale
Abstract : John Snow's investigation of the 1854 cholera outbreak in London is portrayed as a classic example of epidemiology informing real world implementation. The public discourse regarding cholera in Victorian London was more fraught than is generally appreciated today. Snow suspected that cholera was transmitted by contaminated water. At a time when disease was believed to be spread by miasma (foul air), Snow's views were revolutionary. Snow's story will be retold in the person of his friend and colleague Rev Henry Whitehead. 600 of Whitehead's parishioners died in the epidemic. Though initially sceptical of Snow's theories, he investigated the outbreak using his strong network of relationships with the people of Soho, identifying the sentinel case and source of contamination of the Broad Street Well. Snow had died when cholera returned to London in 1865/66, leaving Whitehead the main authority on the Broad Street outbreak. Whitehead worked with the Government Statistician William Farr's staff to identify the source of the outbreak. This time Farr was convinced and took up the cause. Arguably, the real driver for reform may have been political. It was not until the "big stink, " when the heavily contaminated Thames became so disgusting that it threatened to close the newly opened House of Commons, that politicians found the motivation to pass legislation ensuring clean water. The ferocious public discussion regarding cholera in Victorian England has many parallels with contemporary public health debates. While Snow's theories have subsequently been proven, he did not win the argument. Others who were more politically savvy and socially better connected did that. " Dr Snow's views on cholera, " said a medical friend to me in 1855, " are generally regarded in the profession as very unsound. If that be the case, " I replied, " then heresy may be as good a thing in your profession as some of you are apt to suppose it is in mine. " Reverend Henry Whitehead (1825–1896).